PENGGUNAAN PROJECT BASED LEARNING (PBL) BERBANTUAN EDPUZZLE DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK SMA - Zusuf Amien; Muhammad Nurwahidin; Dwi Yulianti; Ari Nurweni; Muhammad Sukirlan (Media Bina Ilmiah, 2023)
The development of scientific learning models is now growing rapidly, including the project based learning program with the aim of Edpuzzle in increasing student learning outcomes. The research was conducted to know the learning outcomes of students through the project based learning assisted Edpuzzle-. A good learning model is a type of learning that enable student to improve outcomes learning with the help of information technology. The research method in this research is in the form of the SLR (Systematic Literature Review) method. Data were collected by reviewing national journals that have been accredited by Sinta and Google Scholar. Information selection was carried out by analyzing all articles about the project based and Edpuzzle in the 2015-2022 timeframe. The articles selected in this review are 10 articles found from Google Scholar and SINTA .The result of this study are the type of learning Project Based Learning (PBL) Edpuzzle in individual or group learning processes to improve student learning outcomes.